The Effect of Age on von Willebrand Factor and Bleeding Symptoms in von Willebrand Disease - Seaman, Craig D.; Ragni, Margaret V. (Thrombosis and Haemostasis, 2020)
von Willebrand disease (VWD) is a quantitative or qualitative defect in von Willebrand factor (VWF) resulting in mucocutaneous bleeding symptoms and hemorrhage following hemostatic challenges, such as trauma or surgery. VWD-specific therapy, DDAVP (1-desamino-8-D-arginine vasopressin) and VWF concentrates, is necessary periprocedurally to ensure adequate hemostasis. The aging VWD patient may complicate this matter. The plasma concentration of many coagulation proteins, including VWF, increases with age. While it has been established that VWF levels increase with age in a healthy population, emerging research demonstrates this occurs in certain subtypes of VWD, too. Thus, the management of periprocedural VWD-specific therapy in the aging VWD patient is problematic when VWF levels increase over time to normal, and hematologists are left with uncertainty regarding whether or not periprocedural VWD-specific therapy is still necessary. In this article, we will review the current state of the literature regarding the effect of age on VWF levels in the healthy population and VWD while exploring possible etiologies for this phenomenon. Further, we will detail how this affects bleeding symptoms and highlight what research remains to be done to optimize care in this patient population.
Keywords: von Willebrand disease; von Willebrand factor; age; bleeding score